1998
DOI: 10.1111/j.1095-8649.1998.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among dominance status, metabolic rate and otolith size in masu salmon

Abstract: In spatial competition between individuals, neither fish sex nor body mass affected dominance status in masu salmon Oncorhynchus masou. In contrast, resting metabolic rate (M R ) was significantly correlated with dominance status, indicating that a high metabolic rate can increase the dominance rank of juvenile salmon. Whole animal growth rate was significantly correlated with M R , but not with initial body weight. This suggests that the body size of masu salmon is not a cause, but rather a consequence, of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(81 citation statements)
references
References 22 publications
7
66
6
Order By: Relevance
“…Male dominance in some lizard species also appears to be influenced by locomotor function, with enhanced locomotor performance increasing the likelihood of territorial dominance (Garland et al 1990;Perry et al 2004;Robson and Miles 2000). Metabolic rate similarly appears to be related to social dominance in fish (Metcalfe et al 1995;Priede 1985;Yamamoto et al 1998). Rather than disparate views, we suspect that these two perspectives, behaviorally proactive and enhanced metabolic and/or locomotor performance, may both be influenced by similar neural and endocrine machinery (Emerson et al 2000;Waters et al 2005).…”
Section: Discussionmentioning
confidence: 92%
“…Male dominance in some lizard species also appears to be influenced by locomotor function, with enhanced locomotor performance increasing the likelihood of territorial dominance (Garland et al 1990;Perry et al 2004;Robson and Miles 2000). Metabolic rate similarly appears to be related to social dominance in fish (Metcalfe et al 1995;Priede 1985;Yamamoto et al 1998). Rather than disparate views, we suspect that these two perspectives, behaviorally proactive and enhanced metabolic and/or locomotor performance, may both be influenced by similar neural and endocrine machinery (Emerson et al 2000;Waters et al 2005).…”
Section: Discussionmentioning
confidence: 92%
“…Early studies found a correlation between otolith growth and temperature (Mosegaard et al 1988), which indicated a relationship between fish metabolism and otolith growth. This idea was substantiated by studies finding a correlation between standard or resting metabolic rate and otolith growth (Wright 1991;Yamamoto et al 1998;Neat et al 2008). However, Wright et al (2001) did not find a simple proportionality between resting metabolic rate and otolith growth, suggesting that additional factors are important.…”
Section: Otolith Growthmentioning
confidence: 96%
“…Studies examining the relationship between otolith increment widths and metabolic rates eventually led to the conclusion that the proportionality observed in most studies was due to a common dependence on metabolic processes Yamamoto et al 1998;Armstrong et al 2004;Bang and Grønkjaer 2005). In short, processes related to the metabolism of fish govern both fish and otolith growth and give rise to the observed proportionality of otolith and fish size.…”
Section: Otolith Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In fights between pairs of size-matched, first-feeding Atlantic salmon (Metcalfe et al 1995) and rainbow trout (McCarthy 2001), the individual with the higher resting metabolic rate is most likely to win. In juvenile masu salmon (Oncorchynchus masou) there is a significant positive relationship between resting metabolic rate and the ability of fish to monopolise large profitable territories (Yamamoto et al 1998). Compared to subordinates, dominant juvenile Arctic charr, which have high resting metabolic rates, also have higher activity of enzymes involved in respiratory metabolism in their muscles (Le Francois et al 2005).…”
Section: The Role Of Metabolic Physiology and Nutritional Statusmentioning
confidence: 99%